Compact Polarization-Independent MMI-Based 1 $×$ 2 Power Splitter Using Metal-Cap Silicon-on-Insulator Waveguide - Chao Pan; B. M. A. Rahman (IEEE Photonics Journal)
A compact polarization-independent multimode interference (MMI)-based 1 $×$ 2 power splitter is designed by introducing a metal-cap silicon-on-insulator (SOI) waveguide as the MMI section, and its polarization and attenuation characteristics are optimized by using a full-vectorial $H$ -field finite-element method (FEM). The least square boundary residual method is used to study the propagation process and the dependence of the image quality on the number of modes used. It is shown that a 330-nm-high, 5- $μ\text{m}$ -wide, and 24.54- $μ\text{m}$ -long MMI section can yield a polarization-independent 1 $×$ 2 power splitter with the excess loss of only 0.66 and 0.86 dB for the quasi-transverse electric (TE) and quasi-transverse magnetic (TM) modes, respectively.